What Non-Muslims Say About Halal-Certified Products? - Annisa, Arna Asna; Hartiningsih, Sepia; Kholifah, Siti; Rahmawati, Fatimah; Iskandar, Iskandar (Journal of Digital Marketing and Halal Industry, 2022)
The growth of the halal industry can be influenced by consumer behavior towards purchasing decisions for halal products. On the other hand, people's halal consumption patterns are influenced by halal literacy in heterogeneous societies. This study aims to find out how the attitudes of non-Muslim communities in Salatiga City regarding halal-certified products. The research method used is a qualitative method and is descriptive. The sample for this research was taken from 5 non-Muslim residents in the City of Salatiga who represented Catholicism, Protestant Christianity, Hinduism, Buddhism and Confucianism. This field research was carried out by asking questions through interviews with informants. The results of the study showed that the interviewees stated that they strongly agreed to choose halal-certified products, chose useful products and considered halal-certified products to be products with guaranteed quality and cleanliness. The resource person is neutral in feeling anxious when not consuming halal-certified products, and in choosing products that are not halal-certified. The concern of resource persons for halal-certified products is general in nature, each resource person has many considerations. Based on the research results, this can be used as a recommendation for halal literacy policies for heterogeneous communities. with a socio-cultural approach